On the approach to one weight concept in mechanics - Kulviecas, L. (Psichologija, 1966)
The article analyses one of the definitions of weight concept which is based on the earth gravity force F decomposition into two components – centrifugal force and weight force. Though this method of definition in scientific-theoretical literature is very rare, it is entrenching in the elementary mechanics, and is included into secondary school textbooks.The article shows that this kind of decomposition of force F to two vectors is not always possible in the inertial reference system which is studied in high school physics course.In order to supply with the correct weight definition, it is important to introduce the reference system that is related to rotating earth.
Keywords: weight; centrifugal force